2004
DOI: 10.1074/jbc.m404584200
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern Recognition Serine Proteinase Triggers the Prophenoloxidase Activation Cascade in the Tobacco Hornworm, Manduca sexta

Abstract: A serine proteinase cascade in insect hemolymph mediates prophenoloxidase activation, a defense mechanism against pathogen or parasite infection. Little is known regarding its initiating proteinase or how this enzyme is activated in response to invading microorganisms. We have isolated from the tobacco hornworm, Manduca sexta, a cDNA encoding a modular protein designated hemolymph proteinase 14 (HP14). It contains five low density lipoprotein receptor class A repeats, a Sushi domain, a unique Cys-rich region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 36 publications
4
86
0
Order By: Relevance
“…Based on these data, we concluded that: 1) the amino-terminal light chain of HP21 (Ala 1 to Leu 152 ) began at the predicted starting site of mature proHP21 (Fig. 1); 2) HP14, which cut itself immediately after Leu 387 and hydrolyzed Ala-AlaPro-Leu-p-nitroanilide (Ji et al, 2004), cleaved proHP21 at the predicted activation site between Leu 152 and Ile 153 .…”
Section: Cleavage Activation Of Prohp21 By Hp14mentioning
confidence: 89%
See 1 more Smart Citation
“…Based on these data, we concluded that: 1) the amino-terminal light chain of HP21 (Ala 1 to Leu 152 ) began at the predicted starting site of mature proHP21 (Fig. 1); 2) HP14, which cut itself immediately after Leu 387 and hydrolyzed Ala-AlaPro-Leu-p-nitroanilide (Ji et al, 2004), cleaved proHP21 at the predicted activation site between Leu 152 and Ile 153 .…”
Section: Cleavage Activation Of Prohp21 By Hp14mentioning
confidence: 89%
“…We reported the molecular cloning and functional analysis of M. sexta HP14, a modular serine proteinase containing seven disulfide knotted structures and one catalytic domain (Ji et al, 2004). The recombinant HP14 precursor binds to peptidoglycan, autoactivates, and triggers the proPO activation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to these microbial polysaccharides, HP14 undergoes autoactivation, presumably via an initial conformational change that enables one molecule of HP14 to cleave a second molecule at its activation site (GTEL*VLGG). Key residues in the putative substrate binding pocket of HP14 (Gly 585 , Ala 616 , and Thr 630 ) are consistent with cleavage after a bulky, hydrophobic residue such as leucine (3). The cleaved form of HP14 can initiate activation of proPO in hemolymph (3,4).…”
mentioning
confidence: 83%
“…Until now, only proteinases in the first and final positions of the melanization pathways have been conclusively identified. Just one initiating proteinase has been discovered: Manduca sexta hemolymph proteinase 14 (HP14), which autoactivates in the presence of microbial surface components (3,4). In contrast, several proPO activativing proteinases (PAPs, also named PPAF and PPAE) have been identified through biochemical studies of M. sexta, Holotrichia diomphalia, and Bombyx mori (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation